Developing Writing Ability Through Theme and Rheme of Narrative Text - Widhari, Maulidya Mayang; Risnawaty; Ritonga, Muhammad Yusuf (PT Inovasi Pratama Internasional, 2023)
This research aims (1) To find out the development of students' ability to write narrative texts (2) To find out the dominant type of theme in student writing (3) To find out the factors that influence students' ability to write narrative text. This research is quantitative and qualitative in nature and was conducted in February 2023 to students of class. In this research, samples were taken by means of cluster random sampling of 33 students. Data were collected through tests in the form of narrative texts written by students using themes and rhemes according to the assessment aspect rubric and through pretest and posttest. The pre-test was given to determine students' ability in writing skills before being given treatment, while the post-test was given to determine students' abilities in writing skills after being given treatment. Then the collected data will be presented in the form of descriptions and diagrams. The results showed that the average pretest score was lower than the posttest average score (60.24<81.88). That is, the set of themes and rhymes can develop students' writing skills significantly. From the results of the qualitative description, the type of theme that is most widely used is the type of topical theme with a percentage (84.84%). This was also shown by the questionnaire data before treatment was lower than after receiving treatment with (65.82 <68.48). This study concluded that the theme and rheme sets can develop students' writing skills